2004
DOI: 10.1055/s-2004-832644
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Cardioprotective Effect of Breviscapine During Hypoxia of Cardiomyocytesin vitroand During Myocardial Infarctionin vivo

Abstract: Breviscapine is a flavonoid extracted from Erigeron breviscapus. Hand.-Mazz, and it has been reported that breviscapine can activate K+ channels and block Ca2+ channels. In this paper, we studied the cardioprotective effects of breviscapine on electrocardiogram (ECG) changes (ST-segment elevation), infarction size in dog heart subjected to myocardial infarction caused by left coronary artery ligation and lactate dehydrogenase (LDH) leakage, changes of intracellular free Ca2+ levels, apoptosis and necrosis in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Studies indicated that scutellarin exhibits a variety of pharmacological properties. Its protective efficacy on ischemic hearts in animal studies has been well established (Li et al, 2004). The mechanism may involve the ability of scutellarin to attenuate the increment of intracellular calcium in cultured neonatal ventricular myocytes.…”
Section: Scutellarin (mentioning
confidence: 99%
“…Studies indicated that scutellarin exhibits a variety of pharmacological properties. Its protective efficacy on ischemic hearts in animal studies has been well established (Li et al, 2004). The mechanism may involve the ability of scutellarin to attenuate the increment of intracellular calcium in cultured neonatal ventricular myocytes.…”
Section: Scutellarin (mentioning
confidence: 99%
“…Breviscapine is isolated from the Asteraceae plant E breviscapus and can be prepared as a Chinese patent medicine, where the essential active ingredients are flavones [38,39] . It possesses an anti-platelet and anti-thrombus action and can lower plasma fibrin content and promote fibrinolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 1 could prevent the development of hypoxic pulmonary hypertension by inhibiting the expression and activation of fractalkine [2]. Breviscapine (1) improve cerebral microcirculation and increase cerebral blood flow, inhibit the platelet activation and aggregation, and could prevent thrombosis formation [3]; and also could be in favor of myocardial protection [4]. However, the effects of 1 on pulmonary inflammatory response and lung function in children undergoing open heart surgery were less straightforward.…”
Section: Introductionmentioning
confidence: 99%